2017
DOI: 10.2139/ssrn.2999618
|View full text |Cite
|
Sign up to set email alerts
|

New Results on the Order of Functions at Infinity

Abstract: Recently, new classes of positive and measurable functions, M(ρ) and M(±∞), have been defined in terms of their asymptotic behaviour at infinity, when normalized by a logarithm (Cadena et al., , 2017. Looking for other suitable normalizing functions than logarithm seems quite natural. It is what is developed in this paper, studying new classes of functions of the type lim x→∞ log U (x)/H(x) = ρ < ∞ for a large class of normalizing functions H. It provides subclasses of M(0) and M(±∞).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As in Lemma 2.2, from Cadena, Kratz and Omey [5], we obtain A(x) f (w i (x)) B(x) with A, B ∈ RV θ , and (3.2) follows. Starting from (3.2) we use a property of regular variation: If U (x) ∈ RV α , then ln U (x)/ ln x → α, see [2], to obtain (3.1).…”
Section: An Extensionmentioning
confidence: 78%
See 3 more Smart Citations
“…As in Lemma 2.2, from Cadena, Kratz and Omey [5], we obtain A(x) f (w i (x)) B(x) with A, B ∈ RV θ , and (3.2) follows. Starting from (3.2) we use a property of regular variation: If U (x) ∈ RV α , then ln U (x)/ ln x → α, see [2], to obtain (3.1).…”
Section: An Extensionmentioning
confidence: 78%
“…Cadena, Kratz and Omey [5] showed that (2.4) (with w(n) = n) holds if and only if f (x) = a [x] satisfies the following property.…”
Section: A Simple Log Testmentioning
confidence: 99%
See 2 more Smart Citations